ANALISIS MANAJEMEN RISIKO PEMBANGUNAN SEKOLAH ALAM DI LAHAN GERSANG: STUDI KASUS YPP NURUL FURQON - Prabawati, Tyas; Wulandari, Erni; Suhendi (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
RISK MANAGEMENT ANALYSIS OF NATURAL SCHOOL DEVELOPMENT IN ARROW LAND: A CASE STUDY OF YPP NURUL FURQON Nature schools are an educational model that utilizes direct interaction with the environment as a learning laboratory, allowing students to gain authentic experiences. However, building nature schools in arid areas presents significant challenges due to the arid environmental conditions that do not support vegetation growth, limited water resources, and other risks that have the potential to hinder educational sustainability. This study aims to analyze risk management in the construction of Nurul Furqon Nature Middle School (YPP Nufo) located in Mlagen Village, Pamotan District, Rembang Regency, Central Java. The research method used a qualitative descriptive approach with a case study. Data were obtained through direct observation, in-depth interviews with homogeneous sampling and critical case sampling of 15 people, and literature review. Risk analysis was conducted using a probability and impact matrix (Probability Impact Matrix). The results indicate that there are major risks originating from environmental, social, and economic aspects. Risks with very high priority include extreme temperatures, drought, and plant death, while social risks arise from cultural differences with the local community. Economic risks that arise include high electricity costs and the need for development funds. This study concludes that holistic, adaptive, and inclusive risk management to realize nature schools requires community participation, environmental innovation, and resource diversification to ensure the sustainability of nature school development in arid areas.